Variation in the practice of tracheal intubation in Europe after traumatic brain injury: a prospective cohort study - B.Y. Gravesteijn; C.A. Sewalt; A. Ercole; F. Lecky; D. Menon; E.W. Steyerberg; A.I.R. Maas; H.F. Lingsma; M. Klimek; CENTER‐TBI collaborators (WILEY, 2022)
Traumatic brain injury patients frequently undergo tracheal intubation. We aimed to assess current intubation practice in Europe and identify variation in practice. We analysed data from patients with traumatic brain injury included in the prospective cohort study collaborative European neurotrauma effectiveness research in traumatic brain injury (CENTER-TBI) in 45 centres in 16 European countries. We included patients who were transported to hospital by emergency medical services. We used mixed-effects multinomial regression to quantify the effects on pre-hospital or in-hospital tracheal intubation of the following: patient characteristics; injury characteristics; centre; and trauma system characteristics. A total of 3843 patients were included. Of these, 1322 (34%) had their tracheas intubated; 839 (22%) pre-hospital and 483 (13%) in-hospital. The fit of the model with only patient characteristics predicting intubation was good (Nagelkerke R2 64%). The probability of tracheal intubation increased with the following: younger age; lower pre-hospital or emergency department GCS; higher abbreviated injury scale scores (head and neck, thorax and chest, face or abdomen abbreviated injury score); and one or more unreactive pupils. The adjusted median odds ratio for intubation between two randomly chosen centres was 3.1 (95%CI 2.1-4.3) for pre-hospital intubation, and 2.7 (95%CI 1.9-3.5) for in-hospital intubation. Furthermore, the presence of an anaesthetist was independently associated with more pre-hospital intubation (OR 2.9, 95%CI 1.3-6.6), in contrast to the presence of ambulance personnel who are allowed to intubate (OR 0.5, 95%CI 0.3-0.8). In conclusion, patient and injury characteristics are key drivers of tracheal intubation. Between-centre differences were also substantial. Further studies are needed to improve the evidence base supporting recommendations for tracheal intubation.